Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173877
|View full text |Cite
|
Sign up to set email alerts
|

Share and Share Alike?

Abstract: Interfaces are commonly designed from the perspective of individual users, even though most of the systems we use in everyday life are in fact shared. We argue that more attention is needed for system sharing, especially because interfaces are known to influence coordination of shared use. In this work, we aim to deepen the understanding of this relation. To do so, we design three interfaces for a shared lighting system that vary in the type of social information they allow people to share with others and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…When designing interactions with everyday systems that are shared in use-i.e., systems that are integrated in the routines of people's everyday lives and environments-we feel that designing for awareness deserves even more attention and should become a standard consideration. We can illustrate this argument with our previous work, in which we investigated designing for awareness in interactive lighting systems [92,93]. We designed three interfaces for an interactive office lighting system, which differed in the type of information they allowed people to share among each other through the interface.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…When designing interactions with everyday systems that are shared in use-i.e., systems that are integrated in the routines of people's everyday lives and environments-we feel that designing for awareness deserves even more attention and should become a standard consideration. We can illustrate this argument with our previous work, in which we investigated designing for awareness in interactive lighting systems [92,93]. We designed three interfaces for an interactive office lighting system, which differed in the type of information they allowed people to share among each other through the interface.…”
Section: Introductionmentioning
confidence: 76%
“…We designed three interfaces for an interactive office lighting system, which differed in the type of information they allowed people to share among each other through the interface. Evaluation of the interfaces demonstrated how the availability of information can help people to coordinate shared use among each other, by lowering the threshold for verbal communication, by making social norms more prevalent, and by increasing feelings of accountability [93]. Moreover, we found that when people have too little information about the subjective rules around system sharing, this leads to more conflict-avoiding behavior and fewer interactions with the system [92,93].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations